1974
DOI: 10.1021/jf60192a019
|View full text |Cite
|
Sign up to set email alerts
|

Yellow pigments of Dioscorea bulbifera

Abstract: Mention of a trade name, proprietary product, or specific equipment does not constitute a guarantee or warranty by the tí. S.Department of Agriculture and does not imply its approval to the exclusion of other products that may be suitable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…On the other hand, our X. sagittifolium cultivars displayed no detectable amount of all-trans-b-carotene, contrary to those analyzed by Bradbury and Holloway (1988). Some D. bulbifera cultivars exhibited small quantities of all-trans-b-carotene, whereas it was not detected by Martin et al (1974). Cyrtosperma merkusii (Araceae) studied by Englberger et al (2008) is important for health in the Pacific.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, our X. sagittifolium cultivars displayed no detectable amount of all-trans-b-carotene, contrary to those analyzed by Bradbury and Holloway (1988). Some D. bulbifera cultivars exhibited small quantities of all-trans-b-carotene, whereas it was not detected by Martin et al (1974). Cyrtosperma merkusii (Araceae) studied by Englberger et al (2008) is important for health in the Pacific.…”
Section: Discussionmentioning
confidence: 99%
“…The extraction method utilised up to 20-fold less raw material and less than half the solvent of the commonly applied modified HarvestPlus approach (Champagne et al, 2010;Ferede et al, 2010;Ukom et al, 2014), whilst attaining profiles which matched some of those previously recorded, with many xanthophyll esters, e.g., D. alata (Champagne et al, 2010), D. bulbifera (Martin et al, 1974) and D. cayennensis (Martin & Ruberte, 1975) and stereoisomers present. The scaled-down extraction allowed increased throughput with easier sample handling and, consequently, the relatively long run-time of the HPLC was the limiting factor for the speed of screening.…”
Section: Scaled-down Extraction Methodsmentioning
confidence: 95%
“…However, studies on other varieties of the species have found low carotenoid content (Ukom et al, 2014). The same holds true for the species D. alata and D. bulbifera, where reports conflict regarding carotenoid compositions and quantities of β-carotene (Inocent, Ejoh, Issa, Schweigert, & Tchouanguep, 2007;Lako et al, 2007;Martin, Telek, & Ruberte, 1974;Ukom et al, 2016).…”
Section: Introductionmentioning
confidence: 92%
“…The yellow pigments of the aerial tubers of D. bulbi/era were investigated by Martin et al (1974). Ten varieties grown in Puerto Rico contained carotenoids that consisted exclusively of xanthophylls in free and predominantly esterified form.…”
Section: (Dioscorea Spp) Dioscoreaceaementioning
confidence: 99%